Exercise Addiction Among Youth As a Behavioral Addiction – a narrative review - Paluchowicz, Karolina; Siwicka, Katarzyna; Szewczyk, Konrad; Janasik, Laura; Kociucka, Patrycja; Sadowski, Krzysztof; Modelska, Julia; Jeleń, Anita; Podolska, Anna (Journal of Education, Health and Sport, 2026)
Background. Understanding behavioral addictions, including exercise addiction, is crucial to comprehend their consequences. The development of a behavioral addictions group suggests that current knowledge about dysfunctional activities is incomplete, especially in youth. Aim. The aim of this review was to combine the existing evidence on behavioral addictions, especially exercise addiction, in youth, in the context of evolving classification and the growing trends promoting inappropriate forms of physical activity. Material and methods. We analyzed 111 studies and reviews describing various aspects of exercise addiction in youth, prioritizing mechanisms of development, risk factors, diagnostic and therapeutic methods, based on data from groups of adolescents or young adults. Results. Findings of the review showed that the literature addressing exercise addiction among adolescents is limited. Common mechanisms can be recognized, including those related to personality traits, body self-awareness, and environmental influences. Many risk factors were identified and linked with the type of sport practiced, cultural impacts, and other mental disorders, mostly eating disorders and body image disturbance. Current diagnostic and therapeutic processes, although partially studied among youth, remain unstructured. Discussion. Available sources are based primarily on adults. Due to the specification of adolescence, described findings are insufficient to clearly define the excessive exercise in youth. The development of a unified psychiatric approach, enabling early identification of high-risk individuals and prevention of addiction, is limited. Conclusions. Exercise addiction and other behavioral addictions in youth are a promising topic that requires further research.